PENGARUH SKEPTISME PROFESIONAL, INDEPENDENSI, DAN TEKANAN WAKTU TERHADAP KEMAMPUAN AUDITOR MENDETEKSI KECURANGAN - Sofie Sofie; Nanda Afriandi Nugroho (Jurnal Akuntansi Trisakti, 2018)
This study aims to determine the effect of professional skepticism, independence, and time pressure on the ability of auditors to detect fraud. Subjects in this study are auditors who work in Public Accounting Firm in DKI Jakarta. In this study, a sample of 103 respondents was chosen by convenience sampling method. A total of 103 questionnaires were given then 103 questionnaires were returned and there were 100 questionnaires that could be used and checked using multiple linear regression models, while there were 3 questionnaires that could not be used because there was no answer. Analyzer used in this research is SPSS 22. The results of auditor skepticism and independence have a significant positive effect on auditor fraud detection ability. Time pressure affects the fraud detection ability significantly negatively.